2002
DOI: 10.1111/j.1572-0241.2002.05689.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological markers for prediction of response to anti-tumor necrosis factor treatment in Crohn's disease

Abstract: In this cohort of infliximab-treated patients, neither ASCA nor pANCA could predict response to treatment. However, the combination pANCA+/ASCA- might warrant further investigation for its value in predicting nonresponse in patients with refractory luminal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(70 citation statements)
references
References 23 publications
3
63
0
4
Order By: Relevance
“…ASCAs and P-ANCAs were not associated with response to antitumor necrosis factor-␣ therapy (61 ). A trend toward poor response to anti-tumor necrosis factor-␣ therapy in CD patients carrying the ANCA ϩ /ASCA Ϫ combination has been suggested (61 ). This was, however, not statistically significant and needs to be confirmed.…”
Section: Association With Clinical Phenotypesmentioning
confidence: 38%
See 1 more Smart Citation
“…ASCAs and P-ANCAs were not associated with response to antitumor necrosis factor-␣ therapy (61 ). A trend toward poor response to anti-tumor necrosis factor-␣ therapy in CD patients carrying the ANCA ϩ /ASCA Ϫ combination has been suggested (61 ). This was, however, not statistically significant and needs to be confirmed.…”
Section: Association With Clinical Phenotypesmentioning
confidence: 38%
“…Sanborn et al (60 ) reported that 90% of patients with refractory left-sided colitis were ANCA-positive vs 62% of patients with treatment-responsive UC (P ϭ 0.03). ASCAs and P-ANCAs were not associated with response to antitumor necrosis factor-␣ therapy (61 ). A trend toward poor response to anti-tumor necrosis factor-␣ therapy in CD patients carrying the ANCA ϩ /ASCA Ϫ combination has been suggested (61 ).…”
Section: Association With Clinical Phenotypesmentioning
confidence: 99%
“…A study by Taylor et al ( 45 ) had demonstrated that patients with CD who had a positive p-ANCA were less likely to respond to therapy with infl iximab, and a subsequent result evaluating patients with negative ASCA and positive p-ANCA found a similar trend, although this did not reach statistical signifi cance ( 46 ). Several other studies have since demonstrated similar fi ndings, including a pediatric study ( 47 ).…”
Section: The Role Of Biomarkers Predicting Response To Treatmentsupporting
confidence: 45%
“…Furthermore, failure of anti-TNF therapy with infliximab has been linked to polymorphisms in the TNF/lymphotoxin-alpha region [27] and the pANCA + /ASCA-antibody profile [28]. It is likely the response to other new agents is affected, in many instances, by the genotype of the patient treated.…”
Section: Disease Heterogeneitymentioning
confidence: 99%